1,8-Cineole inhibits biofilm formation and bacterial pathogenicity by suppressing luxS gene expression in Escherichia coli - Wang, Yiming; Zhang, Yu; Song, Xu; Fang, Chunlin; Xing, Rui; Liu, Lu; Zhao, Xinghong; Zou, Yuanfeng; Li, Lixia; Jia, Renyong; Ye, Gang; Shi, Fei; et al. (Frontiers in Pharmacology, 2022)
In recent years, with frequent reports of multi-drug resistant strains, bavteria antibiotic resistance has become an increasingly serious health problem worldwide. One of the most promising ways for combating bacterial infections and antibiotic resistance is development of quorum-sensing (QS) interfering drugs. In this study, the results show that 1,8-cineole inhibited the expression of QS as well as the virulence genes in Escherichia coli O101 (E. coli O101) with a 65% inhibition rate against luxS gene. Therefore, we hypothesized that 1,8-cineole may inhibit the biofilm formation and reduce the pathogenicity of E. coli O101 by inhibiting the expression of luxS gene. To confirm our hypotheses, a luxS gene deleted E. coli O101 was constructed. The results show that the biofilm formation, motility, structure and pathogenicity of E. coli O101 were significantly inhibited following deletion of the luxS gene. In addition, the transcript levels of QS and virulence genes of E. coli O101 were also significantly down-regulated. Interestingly, 1,8-cineole no longer had a significant inhibitory effect on the related phenotype and gene expression of E. coli O101 without luxS gene. In conclusion, the results show that 1,8-cineole can affect bacterial biofilm formation and pathogenicity by suppressing the expression of luxS gene in E. coli O101, which could provide a new perspective for dealing with the biofilm problem of pathogenic bacteria.